Pengembangan Game Edukasi Interaktif Berbasis Wordwall dalam Pembelajaran Fiqih Materi Shalat Subuh Berjamaah Kelas VII - Eva Suriyaningsih; Jasiah Jasiah (Universitas Muhammadiyah Surabaya, 2026)
As the need for engaging and interactive learning media in religious studies increases, the development of technology-based media has become a relevant solution. The background of this research is the importance of using effective media to improve students' understanding of Fiqh material, especially congregational Subuh prayer, so that the learning process becomes more engaging and easier to understand. The purpose of this research is to develop and test the effectiveness of a Wordwall-based educational game as a learning medium for seventh-grade students. The method used is Research and Development (R&D) with a 4D model that includes the Define, Design, Develop, and Disseminate stages. The results of the study indicate that this Wordwall-based educational game media is effective and feasible to use, able to improve students' understanding, motivation, and interest in learning Fiqh material in an interactive and enjoyable manner.